Impact of Stroke Length Variation on Speed Efficiency in an Authomatic Tofu Extract Filtering Machine - Saputro, Danang Dwi; Pangestu, Wahyu Dwi (Rekayasa, 2022)
In the tofu industry, especially at the home-scale "Tahu Pak Muhson," production remains largely manual, with traditional filtering methods. To enhance efficiency, a machine was designed to filter tofu juice, incorporating various crankshaft step lengths to optimize performance. This study aims to assess the impact of different step lengths on filtration time, tofu yield, and quality. Using a descriptive experimental research method with a quantitative approach, the independent variable is crankshaft stroke length (140, 200, 260 mm), while dependent variables include filtration time, yield, and tofu quality. The control variable is a consistent 10kg soybean input. Results indicate that a 260mm stroke length provided the quickest filtration, averaging 524.3 s, compared to 726 s for 140mm and 620 seconds for 200 mm. Yield for the 140mm stroke was 46%, 45.5% for 200mm, and 44.5% for 260 mm. Tofu quality showed minimal variation across different lengths, although the 260 mm stroke length produced tofu with a slightly coarser texture and a faster smell development. The findings demonstrate that step length impacts filtering efficiency and yield, with potential implications for tofu production scalability.